Cyber security in parallel and distributed computing : concepts, techniques, applications and case studies - Le, Dac-Nhuong, 1983-; Kumar, Raghvendra, 1987-; Mishra, Brojo Kishore, 1979-; Khari, Manju; Chatterjee, Jyotir Moy (Scrivener Publishing/Wiley, 2019)
"Covers privacy issue and challenges in data intensive cloud computing environment. Covers the concept of parallel and distributed computing technologies and their applications in real world settings. Offers data processing and security solutions Covers privacy issue and challenges in data intensive cloud computing environment. Includes the latest technologies that cover the major changes and advances of cyber security"--